2015
DOI: 10.1175/jcli-d-15-0376.1
|View full text |Cite
|
Sign up to set email alerts
|

The Sea Level Response to External Forcings in Historical Simulations of CMIP5 Climate Models*

Abstract: Changes in Earth's climate are influenced by internal climate variability and external forcings, such as changes in solar radiation, volcanic eruptions, anthropogenic greenhouse gases (GHG), and aerosols. Although the response of surface temperature to external forcings has been studied extensively, this has not been done for sea level. Here, a range of climate model experiments for the twentieth century is used to study the response of global and regional sea level change to external climate forcings. Both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 52 publications
(61 reference statements)
3
32
0
1
Order By: Relevance
“…The maps show low or negative SLR around the glaciers and ice sheets. As a result of projected changes in the ocean heat content and circulation, there is a dipolar band associated with a shift in the Antarctic Circumpolar Current stretching south of South Africa and Australia [30] and generally higher values in a wide band around the equator in the Indian and Pacific Oceans.…”
Section: Sea-level Projections For 2010-2100mentioning
confidence: 99%
“…The maps show low or negative SLR around the glaciers and ice sheets. As a result of projected changes in the ocean heat content and circulation, there is a dipolar band associated with a shift in the Antarctic Circumpolar Current stretching south of South Africa and Australia [30] and generally higher values in a wide band around the equator in the Indian and Pacific Oceans.…”
Section: Sea-level Projections For 2010-2100mentioning
confidence: 99%
“…In particular, Slangen et al (2015) carried out a detection study of human imprints on sea level patterns. Using the same set of numerical experiments as in Slangen et al (2014), they evaluated the modelled response of sea level to external forcings over the periods 1861-2005.…”
Section: Anthropogenic Signal In Regional Sea Level Trend Patternsmentioning
confidence: 99%
“…Although the physical relationship between the increase in ocean heat content and thermal expansion was appointed to an anthropogenic contribution to sea level rise (e.g., Barnett et al 2005;Gleckler et al 2012), and similarly the observed glacier mass loss and thus its contribution to sea level rise were attributed to human influence, the anthropogenic contributions could not yet be quantified at the time the last report of the IPCC was published. More recent attempts have shed some light on the anthropogenic origin of these two main contributors to global sea level rise and have quantified the human fingerprint for the periods in which there are independent observations (Marcos and Amores 2014;Slangen et al 2014Slangen et al , 2015Marzeion et al 2014). At the regional scale, D&A studies on sea level are highly challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, accurate projections can be made by scaling a fixed pattern with a time-dependent magnitude, as for surface air temperature, but ocean volume-mean temperature is generally a slightly more accurate predictor than global mean surface air temperature for scaling the pattern of sea level change. Recent work has begun to explore the impact of individual radiative forcings (greenhouse gases, aerosols, and natural forcing) on historical sea level change [166].…”
Section: Regional Projections and Emergence Time Of The Forced Signalmentioning
confidence: 99%